A redescription of the Triassic kannemeyeriiform dicynodont Sangusaurus (Therapsida, Anomodontia), with an analysis of its feeding system. (29th November 2017) - Angielczyk, Kenneth D.; Hancox, P. John; Nabavizadeh, Ali
ABSTRACT: The Triassic dicynodont Sangusaurus is poorly known because the holotype of the first species to be described ( S. edentatus from Zambia) is fragmentary, and the description of the second species ( S. parringtonii from Tanzania) is extremely brief. Nevertheless, the genus has played a role in Triassic biostratigraphy by linking the Ntawere Formation and the Manda Beds. Here, we redescribe Sangusaurus, including a new, nearly complete skull from Tanzania. The incomplete holotype of S. edentatus results in few characters diagnosing the genus. The skull of S. parringtonii, however, is highly autapomorphic. The snout is telescoped, with only a thin strip of frontals separating the nasals and the parietals. The external surfaces of the premaxilla, the maxillae, the nasals, and the prefrontals are extremely rugose; a sharp median crest extends from the premaxilla to the frontals, terminating in a thickened boss. The occiput is broader than the skull is long, and the adductor fossa on the squamosal is nearly vertical. Our phylogenetic analysis shows that Sangusaurus is not a kannemeyeriid but instead is a stahleckeriid. The feeding system of Sangusaurus emphasizes an orthal jaw motion. The articular surfaces of the jaw joint form a single posteroventrally sloping surface; translating the quadrate and the articular results in a primarily orthal movement of the jaw symphysis. The internal and external jaw adductors provide a strong, dorsally-directed component to the power stroke. Adductor mechanical advantage is similar to Stahleckeria, but Sangusaurus likely had a stronger transverse component of jaw movement because of the very lateral placement of M. adductor mandibulae externus lateralis. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Angielczyk, K. D., P. J. Hancox, and A. Nabavizadeh. 2018. A redescription of the Triassic kannemeyeriiform dicynodont Sangusaurus (Therapsida, Anomodontia), with an analysis of its feeding system; pp. 189–227 in C. A. Sidor and S. J. Nesbitt (eds.), Vertebrate and Climatic Evolution in the Triassic Rift Basins of Tanzania and Zambia. Society of Vertebrate Paleontology Memoir 17. Journal of Vertebrate Paleontology 37(6, Supplement).